Ultrastructure of ovotestis of young and adult pulmonate mollusk, Macrochlamys indica Benson, 1832. Issue 4 (December 2016) - Roy, Soumen; Chaki, Korak Kanti; Nag, Tapas Chandra; Misra, Kamales Kumar
Abstract: Macrochlamys indica is a hermaphrodite terrestrial pulmonate mollusk. Transmission electron microscope studies were done on the ovotestis of young and adult (older) M. indica which are elaborated in this paper. The ovotestis contains numerous lobes each of which contains many ovoid shaped acini which are occupied by stages of spermatogenesis and a single oocyte. In younger snails, the acini contain stages of developing spermatogenesis, whereas each acinus of older snails is composed of single large oocyte and few stags of spermatogenesis. The number of Sertoli cells is high in the acini of younger snails than in older snails. Details of the cellular organization of the Sertoli cell are described. Some long thin threads extend from the acinar boundary to acinar lumen. The anterior end of these threads is either free or directly connected to the developing cells of spermatogenesis. There are two types of cells in the interacinar space of the ovotestis in both younger and older snails. One cell is small oval interstitial cell and other is thin elongated periacinar cell. The acinar boundary contains secretory cells with deeply stained nucleus. In the acinus of older snails, the Sertoli cells do not form any barrier between oocyte and spermatogenic cells. Functions of the periacinar cell and interacinar cell are discussed. It is found that the spermatogenesis is highly active in younger snails with single dormant oocyte while process of oogenesis predominates in the older snails. The reproductive strategy of this pulmonate species thus depends on the individual's body size and their maturity.